Divergent bitter and sweet taste perception intensity in chronic rhinosinusitis patients. Issue 5 (26th August 2020) - Lin, Cailu; Civantos, Alyssa M.; Arnold, Monique; Stevens, Elizabeth M.; Cowart, Beverly J.; Colquitt, Lauren R.; Mansfield, Corrine; Kennedy, David W.; Brooks, Steven G.; Workman, Alan D.; Blasetti, Mariel T.; Kohanski, Michael A.; et al.
Abstract : Background: Bitter and sweet taste receptors are present in the human upper airway, where they have roles in innate immunity. Previous studies have shown that 1 of the 25 bitter receptors, TAS2R38, responds to specific bacterial signaling molecules and evokes 1 type of a defense response in the upper airway, whereas ligands of sweet receptors suppress other types of defense responses. Methods: We examined whether other bitter taste receptors might also be involved in innate immunity by using sensory responses to bitter compounds that are not ligands of TAS2R38 (quinine and denatonium benzoate) to assess the sensitivity of other bitter receptors in chronic rhinosinusitis (CRS) patients. CRS patients with (n = 426) and without (n = 226) nasal polyps and controls (n = 356) rated the intensity of quinine, denatonium benzoate, phenylthiocarbamide (PTC; a ligand for TAS2R38 ), sucrose, and salt. Results: CRS patients rated the bitter compounds denatonium benzoate and quinine as less intense and sucrose as more intense than did controls (false discovery rate [FDR] <0.05) and CRS patients and controls did not differ in their ratings of salt (FDR >0.05). PTC bitter taste intensity differed between patient and control groups but were less marked than those previously reported. Though differences were statistically significant, overall effect sizes were small. Conclusion: CRS patients report bitter stimuli as less intense but sweet stimuli as more intense than do control subjects. We speculate that taste responses may reflect the competence of sinonasal innate immunity mediated by taste receptor function, and thus a taste test may have potential for clinical utility in CRS patients.